Pontos quânticos semicondutores sintetizados via soluções coloidais aquosas: estudos e aplicações nanobiotecnológicas - Silva, Anielle Christine Almeida (2014)
This work is based on the synthesis of CdSe e CdSe/CdSxSe1-x/CdS magic sized quantum dots, as well as CdSe e CdSe/CdSxSe1-x/CdS ultrasmall quantum dots in aqueous solutions. The physics properties of quantum dots were investigated using various experimental techniques and theoretical models. The modifications in the phonon confinement Gaussian model were done to perform a more realistic description of the shell and the alloy effects in quantum dots CdSe/CdSxSe1-x/CdS in the Raman Spectra. Two methods were developed, one synthesized a quantum dot magic size (MSPQs) and it was able to control the shell thickness CdS around the MSPQs depending on the synthesis temperature, and the second was obtained through the quantum dots ultrasmall, which the thickness of the shell CdS was monitored as a function of the stabilizer concentration. In addition, the results the MSPQs were functionalized with chemicals groups that may be bioconjugated. It was demonstrated that the MSPQs were not immunogenic and did not exhibit cytotoxic effects. Thus, the MSPQs were covalently bond to aspecificantibody for breast cancer targeting its use with a luminescent probe.